TINGKAT KECANDUAN GAME ONLINE DENGAN KONSENTRASI DALAM BERIBADAH PADA REMAJA - Sinaga, Novitasari Br; Siby, Robert R.; Supit, Deisye; Ole, Anita Amelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of online game addiction among adolescents, the level of concentration in worship, and whether there is a significant relationship between the two variables. The independent variable is online game addiction and the dependent variable is concentration in worship. This study employed a quantitative descriptive and correlational design. The sample consisted of 77 Class XI students at SMA Unklab Airmadidi, selected using convenience sampling. Data were collected through the Game Addiction Scale (GAS-21) adapted from Hosnaini (2022) with 19 items, and a worship concentration scale adapted from Siwu (2024) with 9 items. Reliability analysis yielded Cronbach’s alpha of 0.88 and 0.83 respectively. Results revealed that online game addiction was in the moderate category (mean = 2.51), while concentration in worship was in the high category (mean = 3.91). Pearson correlation analysis yielded r = −0.338 with p = 0.003 < 0.05, indicating a significant but low-strength negative relationship between online game addiction and concentration in worship among adolescents. This means the higher the online game addiction, the lower the worship concentration. These findings suggest that while adolescents maintain relatively high worship concentration, the moderate level of game addiction warrants ongoing attention from educators, parents, and church communities.